Arteriovenous fistula creation results in cardiac dysfunction and remodeling in a uremic pig model - Jamie Kane (22633352) (2025)
The arteriovenous fistula (AVF) is required for hemodialysis in end-stage kidney disease (ESKD). AVF creation results in compensatory cardiovascular hemodynamics, which are subsequently associated with cardiac remodeling. Relatedly, cardiovascular mortality and morbidity are elevated in ESKD patients, which worsens in dialysis patients. Currently, no suitable uremic large animal models exist to investigate the mechanisms of AVF-induced cardiac remodeling. This study aims to characterize cardiovascular changes secondary to AVF creation, supported by percutaneous transluminal angioplasty (PTA), in a uremic pig model. Chronic kidney disease (CKD) was induced via renal embolization, followed by AVF creation 28 days later. AVF stenosis was alleviated 28 days thereafter via PTA, and cardiac MRI was performed at 14-, 28-, and 42-days post-PTA. Increased end-diastolic volumes were observed in both ventricles, while systolic function was preserved. LV stroke volume and blood flow through the aorta, pulmonary artery, and vena cava were also increased. In perivascular areas of the LV, senescence markers showed increased p16 expression and decreased p21 expression. The LV showed perivascular fibrosis, with increased cardiomyocyte cross-sectional area, reduced collagen-type IV expression, and MMP2 activity, possibly not driven by TGF-β/CTGF/pSMAD signaling. However, CD4+ or CD68+ cell LV infiltration or inflammatory polarization of resident macrophages were unchanged. In conclusion, AVF creation modified left and right ventricular function and increased peripheral flow, potentially mediated by cellular senescence and fibrosis, resulting in progressive cardiac remodeling. This model may be used to evaluate mechanisms of AVF induced cardiac disease and potentially investigate the efficacy of senolytics and anti-fibrotic agents.